The occurrence of entomopathogenic fungi in apple orchards and their biocontrol potential against Eriosoma lanigerum - Mathulwe, Letodi Luki; Malan, Antoinette Paula; Stokwe, Nomakholwa Faith (African Entomology, 2023)
Eriosoma lanigerum (Hausmann) (Hemiptera: Aphididae), woolly apple aphid (WAA) is an important pest on apples globally and a key pest of apple production in South Africa. The aphid has developed some level of resistance against several chemical insecticides. Entomopathogenic fungi (EPF) have been identified as promising biological control agents against a wide array of insect pests. The main aim of this study was to conduct a survey in local apple orchards in the Western Cape province for EPF and to use isolates to test the susceptibility of WAA under optimum laboratory conditions. Soil samples were collected from apple orchards and EPF, baited and isolated using larvae of Galleria mellonella and Tenebrio molitor. Six EPF species: Beauveria bassiana, Cordyceps fumosorosea, Metarhizium brunneum, M. pinghaense, M. robertsii and Purpureocillium lilacinum were identified from the soil samples. The results from bioassays showed that Metarhizium robertsii and M. pinghaense isolates were the most effective with an average percentage mortality of > 90%. Metarhizium brunneum also proved to be effective when used against the insect with an average percentage mortality of > 80%, while B. bassiana and C. fumosorosea were the least effective with average percentage mortality of 52% and 48%, respectively. The LT50 and LT90 of M. robertsii (2.12; 4.19) and M. pinghaense (2.05; 4.45) showed to require similar mortality time in days of E. lanigerum. The results obtained in the study have provided an insight into the diversity of EPF species across apple orchards of the Western Cape and shown the efficacy of the Metarhizium isolates as potential biological control agents of the WAA.